Time-lapse super-resolution imaging reveals key principles for cis-limited Xist RNA localisation - Rodermund, L (2020)
Dosage compensation in XX female mammals is achieved by X chromosome inactivation (XCI). The key player in this process is the long noncoding RNA Xist (X inactive specific transcript), which associates in cis with the inactive X chromosome elect (Xi) to mediate gene silencing and heterochromatization. Xist spreads across the entire Xi, but little is known about the dynamics of this process, particularly in the context of single cells. This thesis documents the development of a new, time-resolved super-resolution imaging methodology: RNA-SPLIT (Sequential Pulse Localisation Imaging over Time) combining Bgl-stem-loop labelling, HaloTag technology and 3D structured illumination microscopy (3D-SIM) to detect individual Xist RNA molecules in single mouse embryonic stem cells (mESC) with high spatial and temporal resolution.